Menu training and vendor linkages in school feeding programs to support smallholder farmers in Nigeria - Andam, Kwaw S.; Amare, Mulubrhan; Gelli, Aulo; Abay, Kibrom A.; Kosec, Katrina; Bamiwuye, Temilolu; Edeh, Hyacinth O.; Adeyanju, Dolapo; Idowu-Ogundele, Ifetayo; Ekpo, Adaku; Udoh, Nsikak (Social Science Registry, 2024)
The project aims to pilot linking school feeding programs with smallholder farmers who can supply food to school feeding programs. We aim to achieve this through two types of interventions: (i) training of school vendors to improve and tailor school menus; and (ii) creating linkages between school vendors and smallholder farmers. Thus, the project targets both vendors/cooks involved in school feeding programs and potential smallholder farmers who can be linked with school feeding programs. We plan to conduct this pilot study in Osun State, located in the South-West region of Nigeria. Osun is recognized as one of the more successful states in implementing the Nigerian Homegrown School Feeding Program (NHGSFP) and is currently the only state where the program is active. Through this initiative, we aim to generate evidence that can improve program efficiency by analyzing menu plans and procurement procedures. Using this evidence, we intend to collaborate with the Government of Nigeria (GoN) and the World Food Programme (WFP) to extend successful interventions to other states across the country. The primary reference groups for this study are the cooks/vendors and smallholder farmers involved in sales to cooks supported by the school feeding program. We target all cooks involved in school feeding services and smallholder farmers in the targeted communities who are able to supply the food to the cooks, including produce oil-palm, sweet potatoes, yam, cocoyam and vegetables.